Students’ Satisfaction Towards Online Learning at English Education Study Program - Benjamin Jeremias; Helena Magdalena Rijoly; Sophia Binnendyk (Program Studi Pendidikan Bahasa Inggris Kabupaten Kepulauan Aru, 2023)
This study aims to explore students’ satisfaction during online learning process related to 3 aspects which are: Course Structure, Online Learning Flexibility and Technology Quality in English Education Study Program of Pattimura University. This study was conducted with Mixed Method research design using questionnaire as the data collection technique. There were 2 types of questionnaires: Close-Ended Likert Scale questionnaires and Open-Ended Questionnaires. The participants were the active students of English Education Study Program of Pattimura University batch 2017, 2018, 2019 and 2020. The result shows that students’ satisfaction rate is between Satisfied and Satisfied Enough. This means that the satisfaction rate is average. The study also produces a collection of students’ feedbacks and suggestion.